DEVELOPMENT OF RELIGIOUSNESS IN EARLY CHILDHOOD THROUGH FAMILY ISLAMIC RELIGIOUS EDUCATION - Nia Nuraida (Tarbiyat al-Aulad: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
This article aims to elaborate on and discuss initiatives to foster early religious development through family-based religious education. This study employs a literature review methodology, which aims to assess numerous pertinent works on how children's religiosity develops. This study discovered that a number of tactics, including educational strategies, ethical strategies, economic strategies, cultural strategies, and communication strategies, are employed in families in the village to develop children's religiosity through Islamic Religious Education. The goal of educational approach is to help kids become more religious through official, informal, and non-formal education activities. Moral principles formed in rural areas serve as the foundation of ethical strategy. The economic plan intends to raise standards of living and support the domestic sector. The cultural approach involves exposing kids to cultural norms that do not contradict Islamic principles. In order to build religious strength in the face of swiftly changing circumstances, the communication strategy calls for the development of excellent communication between parents and children.